Enhancing Digital Literacy in Eighth-Grade Students through AI-Integrated ProProfs.com and Differentiated Instruction - Prastyo, Nada Tarofil Lubbi; Solihin, Annas; Suhartono, Suhartono; Subrata, Heru; Daoyi, Zheng (Educative: Jurnal Ilmiah Pendidikan, 2024)
Digital literacy is essential for success in the 21st-century education landscape, requiring innovative strategies to address diverse learner needs. This study examines the effectiveness of the Differentiated Instruction (DI) strategy integrated with AI-enabled ProProfs.com in improving eighth-grade students' digital literacy skills. A quasi-experimental design was employed with 60 students divided into an experimental group (30) and a control group (30). Results showed a significant improvement in digital literacy for the experimental group, with an average score increase of 16.7 points (p < 0.0001), compared to 3.4 points in the control group (p = 0.045). ProProfs.com allowed personalized learning, leading to higher motivation and engagement; 85% of students reported increased motivation, and 78% noted better material comprehension. These findings highlight the effectiveness of AI-integrated platforms in differentiated learning, encouraging educators and policymakers to adopt such approaches to enhance digital literacy and cater to diverse educational needs.